Is Africa Different? Historical Conflict and State Development. Issue 2 (4th May 2019) - Dincecco, Mark; Fenske, James; Onorato, Massimiliano Gaetano
ABSTRACT: We show new evidence that the consequences of historical warfare for state development differ for Sub-Saharan Africa. We identify the locations of more than 1, 600 conflicts in Africa, Asia, and Europe from 1400 to 1799. We find that historical warfare predicts common-interest states defined by high fiscal capacity and low civil conflict across much of the Old World. For Sub-Saharan Africa, historical warfare predicts special-interest states defined by high fiscal capacity and high civil conflict. Our results offer new evidence about where and when 'war makes states'.